The value of mass-digitised cultural heritage content in creative contexts. Issue 1 (April 2021) - Terras, Melissa; Coleman, Stephen; Drost, Steven; Elsden, Chris; Helgason, Ingi; Lechelt, Susan; Osborne, Nicola; Panneels, Inge; Pegado, Briana; Schafer, Burkhard; Smyth, Michael; Thornton, Pip; et al.
How can digitised assets of Galleries, Libraries, Archives and Museums be reused to unlock new value? What are the implications of viewing large-scale cultural heritage data as an economic resource, to build new products and services upon? Drawing upon valuation studies, we reflect on both the theory and practicalities of using mass-digitised heritage content as an economic driver, stressing the need to consider the complexity of commercial-based outcomes within the context of cultural and creative industries. However, we also problematise the act of considering such heritage content as a resource to be exploited for economic growth, in order to inform how we consider, develop, deliver and value mass-digitisation. Our research will be of interest to those wishing to understand a rapidly changing research and innovation landscape, those considering how to engage memory institutions in data-driven activities and those critically evaluating years of mass-digitisation across the heritage sector.